Education on the Importance of 5R Culture For CNC Workers at CV. Rahayu Sentosa - Irfansyah, Daffa Anizar Irfansyah; Sahri, Moch; Istiar, Bayu; Ratriwardhani, Ratna Ayu; Firmansyah, Ari Adam (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Therefore, this socialization was prepared with the aim of implementing the importance of 5S culture in a company, especially in CV. The importance of this culture is applied to increase effectiveness, electability and efficiency related to work culture in the work environment. The method applied in this socialization activity is to conduct field observations and identify the hazard factors in each production process. During the observation process, the authors also conducted interviews through direct question and answer to employees of the CNC Machine Worksop division. The biggest increase was 63% and the smallest increase was 0%. So the outreach activities regarding 5S culture were successful with an average score of 82 with a total increase of 16.5 which met the good to very good categories, namely 60-80 and 80. It is necessary to implement and cultivate the 5S culture so that it sticks with workers at CV. Rahayu Sentosa to support the safety and comfort of workers in every production process.